AFL Students' Motivation toward Learning Arabic in Jordan as Related to Some Variables - Al- Khawaldeh, Mohammad; Al-JArah , Abdelnasser; Al-Rabiea, Faisal (Jordan Journal of Educational Sciences, 2014)
This study aimed at investigation the foreign students' motivation level toward learning Arabic, and whether would be statistical significant differences at the level (α = 0.05) in their motivation due to the variables of: student's gender, his nationality and the period of time that he spent in Jordan. To achieve the aims of the study a (Manusak 2010) foreign language learning motivation scale was adopted. The scale consisted of (20) items equally distributed on instrumental and integrative motivation domains. The sample of the study consisted of (90) male female students who belong to various nationalities from who enrolled in teaching Arabic for non native speakers program in the language centers of Jordanian and Yarmouk universities in the end of 2nd semester 2012/2013. The results of the study revealed that the students' motivation level toward learning Arabic was high. The results also revealed that there were no statistical significant differences in their motivation total score due to the variables of student's gender, to his nationality, and to the period of time he spent in Jordan. Regarding to the scale domains, the results revealed that there were statistical significant differences in the students' instrumental motivation level due to the variable of nationality between Korean students on the one hand, and between American and European Union students on the other hand, in the favor of Korean students. And there were statistical significant differences in students' integrative motivation level between American students on the one hand, and between Korean and European Union students on the other hand, in the favor of American students. The results also revealed that there were no statistical significant differences in students' instrumental and integrative motivation levels due to the variables of gender and period of time